Urticaria Clinical, Diagnostic and Therapeutic Aspects - Henz, Beate M.; Zuberbier, Torsten; Grabbe, Jürgen; Monroe, Eugene (Springer Berlin Heidelberg, 1998)
This book provides a practical, comprehensive review of all clinical aspects and causes as well as the diagnosis and therapy of different types of urticaria. The various chapters deal with acute and chronic urticaria, angioedema, physical urticaria, contact urticaria, pseudoallergic reactions, urticarial vasculitis and mastocytosis. The book is a revision of a monograph which appeared in 1986 and which was since revised twice, particularly regarding newer insights regarding the possible causes of and novel therapeutic approaches to urticaria. The book will hopefully be a practical help in the management of patients with urticaria for physicians specialized in dermatology, allergology, internal medicine, pediatrics and general medicine alike
Keywords: Dermatology; Allergology; Pediatrics; Internal Medicine; Allergy; Internal medicine; Nesselsucht; Aufsatzsammlung